Improvement of Pasteurella multocida serotype B:2 draft genome sequence and analysis of its genome structure and function - Yap, Huan Yong (2013)
Pasteurella multocida serotype B:2 and E:2 are the main causative agents of hemorrhagic septicaemia (HS) in ruminants. Hemorrhagic septicemia is an acute,fatal and septicemic disease of economic importance in tropical regions of the world especially in Asian and African countries. To date, the available vaccines are unable to induce long term immunity and require individual injection which is not feasible since animals normally live in large wild herds or kept semi-wild by the farmers. The molecular basis for pathogenesis of HS caused by P. multocida during natural infections is still vague. Thus, there is an imminent need for whole genome sequencing of HS causing strain as the first step towards understanding of the pathogenicity of P. multocida in causing HS in infected ruminants. Hence, in previous study, the genome of P. multocida serotype B:2 strain PMTB isolated from a dead buffalo during an outbreak of HS in Kelantan, Malaysia, year 2003 was sequenced using Illumina Genome Analyzer. Approximately 7.2 million single end reads with data size 250 MB and an average length of 35 bp was generated, providing ~100 fold genome coverage. De novo assembly using software Velvet produced scaffold with 2191094 bp in length and 89 genome gaps. In this study,Polymerase Chain Reaction (PCR) sequencing approach was used and successfully closed 80 genome gaps with 9 unresolved gaps. The 9 remaining unresolved gaps were due to the large length of the gaps, repeat sequence related or missasemblies of contigs. The predicted total length of the remaining unresolved gap was about 215 k bp, which is impossible to amplify in PCR assay even by using pfu polymerase that specialize in long range PCR. The misassembled contigs and repeat sequence related gaps caused no amplification in PCR assay or the sequences obtained were unable to map to the targeted region. The improved scaffold with 2203419 bp in length with G + C content of 40.46 % was submitted to Prokaryotic Genome Annotation Pipeline (PGAAP) provided by National Center for Biotechnology Information (NCBI) for gene prediction and annotation. The genome was predicted to contain 2021 Coding DNA Sequences (CDSs), 51 tRNA genes and 10 rRNA genes. The toxA gene that encodes dermonecrotic Pasteurella multocida toxin (PMT) which was frequently associated with serogroup D was absent in the strain PMTB genome. The absence of toxA in strain PMTB was validated by PCR assay detection. In addition, integrative conjugative element of Pasteurella multocida, ICEPmu1 which was detected in P. multocida strain 36950 (serogroup A) was found absent in the genome of strain PMTB via sequence similarity search. HTH-type transcriptional regulator for conjugative element sulfamethoxazole/trimethoprim (SXT), another type of integrative conjugative element that originally derived from Vibrio cholera was predicted present in strain PMTB. Further analysis at the locus of predicted SXT element in strain PMTB showed that a large chunk of DNA fragment in the middle part that supposedly harbored antibiotic resistance genes was missing due to unresolved genome sequence gap. However, 12 genes that play important roles in transposase, regulatory and conjugative transfer located in the left and right ends of the element were present in the SXT genome of strain PMTB. Antibiotic susceptibility test (AST) was performed to determine the function of antibiotic resistance genes carrying by SXT element by using disk diffusion method. The AST results showed that strain PMTB resistant to streptomycin (inhibition zone diameter=10.54 mm) only. Strain PMTB was susceptible to chloramphenicol (inhibition zone diameter=25.56 mm), gentamycin (inhibition zone diameter=15.77 mm) and SXT (inhibition zone diameter= 24.31 mm). In addition, strain PMTB was shown that intermediate sensitivity to kanamycin (inhibition zone diameter=17.85 mm) and erythromycin (inhibition zone diameter=18.49 mm). Findings from this study provide valuable information for future studies in the identification of virulence-associated genes to elucidate the pathogenicity of P. multocida strain PMTB.